2022
DOI: 10.1111/1365-2745.14022
|View full text |Cite
|
Sign up to set email alerts
|

Plant species biogeographic origin shapes their current and future distribution on the world's highest island mountain

Abstract: Holme et al., 2015). At higher elevations increased temperature may increase diversity but with limits imposed by available area as mountains taper (Dullinger et al., 2012;Elsen & Tingley, 2015). In addition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Borneo, Sumatra, Java, Mainland Asia) are more likely to occur in warmer lowlands and species of Sahul origin (New Guinea and Australia) species are more likely to occur in cooler higher elevation sites. Trethowan et al's (2023) In Journal of Ecology, Harris et al (2023) compiled traits of African angiosperm species to estimate trait hypervolumes. They then used hierarchical clustering to identify 12 potential biogeographic regions and map them.…”
Section: The Impac Ts Of G Lobal Chang E On G Ene Ti C D Iver S It Y ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Borneo, Sumatra, Java, Mainland Asia) are more likely to occur in warmer lowlands and species of Sahul origin (New Guinea and Australia) species are more likely to occur in cooler higher elevation sites. Trethowan et al's (2023) In Journal of Ecology, Harris et al (2023) compiled traits of African angiosperm species to estimate trait hypervolumes. They then used hierarchical clustering to identify 12 potential biogeographic regions and map them.…”
Section: The Impac Ts Of G Lobal Chang E On G Ene Ti C D Iver S It Y ...mentioning
confidence: 99%
“…In this Special Feature, Shirey et al (2023), in Methods in Ecology and Evolution , develop a set of best practices and a workflow to look at how changes in the occupancy and detection of species, along with collector frequency, influence model performance for datasets with presence‐only records. Trethowan et al (2023) in Journal of Ecology , use over 7000 herbarium specimens to assess how current and future climate change interact with biogeographic origin to shape species occurrence and richness of plants on Mount Jaya, in New Guinea, the tallest mountain on any island in the world. They found that species of Sunda origin (i.e.…”
Section: The Impacts Of Global Change On Genetic Diversity Ranges or ...mentioning
confidence: 99%
See 1 more Smart Citation
“…2) supports the ongoing interchange of Asian and Australian biotas (Sniderman & Jordan, 2011; Morley, 2018; Kooyman et al ., 2019; Joyce et al ., 2021), a celebrated topic in biogeography since Wallace's seminal observations (Wallace, 1860). The diversity of austral plant lineages in Malesia and their general increase in abundance at higher elevations have been discussed since before plate tectonic theory (Stapf, 1894; Richards, 1943; van Steenis, 1964; Ashton, 2014; Brambach et al ., 2020; Trethowan et al ., 2022). The early phases of the collision (Fig.…”
Section: Southern Trees From Deep Timementioning
confidence: 99%
“…Distributional patterns from a recent vegetation analysis of Mt. Jaya, Indonesian New Guinea, also show an increased prevalence and local dominance of southern‐sourced lineages with increasing elevation (Trethowan et al ., 2022).…”
Section: Southern Trees From Deep Timementioning
confidence: 99%